Variation in soil macro-fauna diversity in seven humus orders of a Parrotio-Carpinetum forest association on Chromic Cambisols of Shast-klateh area in Iran - Izadi, M.; Habashi, H.; Waez-Mousavi, S. M. (Eurasian soil science, 2017)
Soil biodiversity includes organisms which spend a part or all of their life cycle on or in the soil. Among soil-dwelling animals, macro-fauna as an important group of animals have important effects on the dynamics of soil organic matter and litter decomposition process. The humus forms interact with the climatic conditions, flora, as well as soil fauna, and microbial activity. In new humus form classifications, soil organisms play an important role in separation of humus horizons from one another. The subject of this study was to determine the diversity of macro fauna for different humus forms. We determined humus forms using morphological classification, and then 69 random samples were taken from plots of 100 cm 2 in area, and soil macro-fauna species were collected by hand sorting method. Two classes of humus forms, including Mull (with three humus orders, namely Dysmull, Oligomull, and Mesomull,) and Amphi (with four humus orders, namely Leptoamphi, Eumacroamphi, Eumesoamphi, and Pachyamphi) were identified. A number of 13 macro-fauna orders were identified using identification key. Among the humus orders, Shannon diversity, Simpson evenness and Margalef richness indices were the highest in Pachyamphi order. Arthropod diversity in Pachyamphi humus order was higher than those of Mull. These results showed that diversity of soil macrofauna increase by increasing the thickness of the organic horizons (OL, OF, OH), especially OH horizon.